2007
DOI: 10.1090/s0002-9947-07-04125-6
|View full text |Cite
|
Sign up to set email alerts
|

An analogue of the Descartes-Euler formula for infinite graphs and Higuchi’s conjecture

Abstract: Abstract. Let R be a connected 2-manifold without boundary obtained from a (possibly infinite) collection of polygons by identifying them along edges of equal length. Let V be the set of vertices, and for every v ∈ V , let κ(v) denote the (Gaussian) curvature of v: 2π minus the sum of incident polygon angles. Descartes showed that v∈V κ(v) = 4π whenever R may be realized as the surface of a convex polytope in R 3 . More generally, if R is made of finitely many polygons, Euler's formula is equivalent to the equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 8 publications
1
105
0
5
Order By: Relevance
“…Because Riemannian manifolds of positive sectional curvature κ uniformly bounded from below as κ(m) ≥ κ min > 0, ∀m ∈ M, have bounded diameter, and because graphs with positive local combinatorial curvature are finite [9,24,7], it follows that, at large scale, only nonpositive curvature is relevant. To define such a concept, let (X, d) be a geodesic metric space.…”
Section: Large Scale δ-Hyperbolic Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Riemannian manifolds of positive sectional curvature κ uniformly bounded from below as κ(m) ≥ κ min > 0, ∀m ∈ M, have bounded diameter, and because graphs with positive local combinatorial curvature are finite [9,24,7], it follows that, at large scale, only nonpositive curvature is relevant. To define such a concept, let (X, d) be a geodesic metric space.…”
Section: Large Scale δ-Hyperbolic Spacesmentioning
confidence: 99%
“…First, it is easily observed that the complete graph is positively curved by the intuitive clustering coefficient definition of [8]. From a more precise standpoint, as a consequence of [7,Theorem 1.7], K n has a 2-cell embedding in either S 2 of PR 2 . As far as isometric embedding is concerned, the following can be said (see [15]): It turns out that K n is also positively curved by our definition: indeed, it is readily verified that ∀ K n ,…”
Section: Proof Consider a Euclidean Trianglementioning
confidence: 99%
“…DeVos and Mohar [8] obtained the following Gauss-Bonnet inequality (3.1), which solves a conjecture of Higuchi [11]. Higuchi's conjecture can be thought of as a combinatorial analogue of Myers' theorem [4,14] on Riemannian manifolds.…”
Section: The Characterization Of Embedded Graphs With Nonnegative Commentioning
confidence: 90%
“…For the motivation of combinatorial curvature, we refer to Gromov [10], Higuchi [11], and Ishida [12]. For the application of the Gaussian curvature and the combinatorial curvature on surfaces, we refer to the recent work of DeVos and Mohar [8] and the author's joint work with G. Chen [7].…”
Section: Vertices 1-cells Open Segments and 2-cells Open Convex Polmentioning
confidence: 99%
“…We then have the Gauss-Bonnet formula of G of [9], We can also compare the combinatorial curvature with another version of curvature naturally obtained from the surface S(G), its generalized sectional (Gaussian) curvature. It turns out that the semiplanar graph G has nonnegative combinatorial curvature precisely if the polygonal surface S(G) is an Alexandrov space with nonnegative sectional curvature, i.e.…”
Section: Let χ(S(g)) Denote the Euler Characteristic Of The Surface Smentioning
confidence: 99%